Metodología para la aplicación de la WEBQUEST en entornos virtuales de aprendizaje para la comprensión de textos en inglés - Mullo Naula, Luis Jairo (2022)
ABSTRACT The research presents the results of the use of the WebQuest as a support tool for the comprehension of texts in English of children of 8th grade of Basic General Education, it is intended to determine the influence of this resource on the academic performance of the study participants. and their perception of the usability of the products developed. The work is a reference on the use of active methodologies in the classrooms of Ecuador and also makes up for the prevailing lack of research that guides the use of this type of technological tools in the classroom. As a study method, a qualitative research approach was used where data collection was carried out through the application of a survey on the perception of the use of the WebQuest applied both to the children participating in the study and to the teachers of the language area. . In addition, a quantitative analysis is carried out that allows comparing the academic performance of the students before and after using the developed resources, the performance of the experimental group compared to the performance of a control group was also contrasted. The results indicate that, in both cases (pvalue = 3.13303E-06 < 0.05) and (pvalue = 0.00192 < 0.05), the use of the learning objects developed significantly improved the academic performance of the students who used the Webquest in their classes. of English. The application of this type of resources facilitated the learning processes of the children participating in the study, making the teachers innovate the way in which they teach their classes, a fact that also allowed them to capture and maintain the attention of the students, who showed themselves motivates and actively participates in the proposed activities with the developed Webquests.